If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -15 = (2x + 1) + x Reorder the terms: -15 + -9x = (2x + 1) + x Reorder the terms: -15 + -9x = (1 + 2x) + x Remove parenthesis around (1 + 2x) -15 + -9x = 1 + 2x + x Combine like terms: 2x + x = 3x -15 + -9x = 1 + 3x Solving -15 + -9x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -15 + -9x + -3x = 1 + 3x + -3x Combine like terms: -9x + -3x = -12x -15 + -12x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -15 + -12x = 1 + 0 -15 + -12x = 1 Add '15' to each side of the equation. -15 + 15 + -12x = 1 + 15 Combine like terms: -15 + 15 = 0 0 + -12x = 1 + 15 -12x = 1 + 15 Combine like terms: 1 + 15 = 16 -12x = 16 Divide each side by '-12'. x = -1.333333333 Simplifying x = -1.333333333
| -12x+43=-7x+28 | | 4x-10=2x(2-5) | | 10*40+3= | | 4=-2(x+11) | | y^2(x-9)+1(x-9)=0 | | 1.5=x/6.5 | | 6a-4=2a+76 | | -2(t-4)+8t=4t-5 | | 5x+2y=98 | | -8(a,8-2)=26 | | 3x+201=153 | | 2.2+x=-4.7 | | n-(-1.2)=-9.3 | | 6z-62z+2=0 | | 6+4n=n-11 | | 4x/x-7-3x/x-3 | | 7(s-5)=43 | | 0=5x^2-10x-4xy+8y | | .3(x+2)-0.5(x+2)=.02x-.04 | | 5x-8=7x-6 | | 6(-4+5h-5-3h)= | | 6[6-(-7x-3)]=168x+108 | | 3n^2+9x+9=3 | | 3x-0.1=0.2-0.4(7-2x) | | 2x/2=0/2 | | 13-2m=19 | | 9x+36=81 | | 8x-12-5x+7=19 | | 4a+15bc+12b+5ac= | | 4(x+2x)=-24 | | -9x+9y=-5-3y | | b-6.2=-8 |